Agronomic assessment of an industrial biosolid for corn crop - Trannin, Isabel Cristina de Barros; Siqueira, José Oswaldo; Moreira, Fátima Maria de Souza (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the agronomic feasibility of an industrial biosolid for corn. The experiment was carried out on a dystrophic Cambisol in two cropping seasons, 1999/2000 and 2000/2001. The application of 0, 6, 12, 18 and 24 Mg ha-1 of biosolid dry matter basis, supplemented with K2O in both trials and with 1/3 of the recommended P2O5 rate in the second trial was compared to the complete mineral fertilization. Biosolid application enhanced soil fertility, crop nutrition and grain productivity. Yield response to doses was quadratic, and reached the maximum of 9,992 kg ha-1 with 22.5 Mg ha-1 of biosolid, 21% higher than the complete mineral fertilization and 74% higher than the control with no fertilizer added. Even in the largest biosolid dose, no symptom of nutrients, sodium or heavy metals toxicity was found. The equivalence in productivity to the mineral fertilization (7,895 kg ha-1) was attained with 10 Mg ha-1 of biosolid. Based on this equivalence to NPK, the biosolid fertilizer value was estimated in R$ 43.70 per Mg for dry residue and in R$ 8.74 per Mg for wet material. Considering transportation costs, biosolid application in corn crop is economically feasible on a distance comprising 66 km from the generating source.